Dual exceptionalities: Exploratory analysis of experiences and self-image in Chilean students - Gómez Arizaga, María Paz (2016)
This research explores the manifestation of dual exceptionality, regarding self-image and the experiences students have had with classmates and teachers. The sample was comprised of four students ages 8 to 15 that exhibited ADHD with giftedness and ASD with giftedness. In-depth interviews were conducted with the students. Results showed that students who had a notion of their discrepancies were motivated towards learning, but became bored when tasks were not challenging. They also had good relationships with their teachers and peers. However, meaningful social interactions had a negative connotation for the gifted/ASD group. Implications for research and practice are discussed further.